(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
A common medication for Type 2 Diabetes Mellitus and related cardiovascular and renal conditions is dapagliflozin, an SGLT2 inhibitor. The purpose of the current work was to establish and validate a straightforward, reliable, accurate, and RP-HPLC method for quantitatively measuring dapagliflozin in tablet dosage forms. A 150 × 4.6 mm, 5 μm C18 column with a mobile phase consisting of phosphate buffer and acetonitrile (60:40, v/v) at isocratic conditions was used to accomplish chromatographic separation. Detection was done at 220 nm while the flow rate was kept at 1.4 ml/min. With a retention time of roughly 4.4 minutes, the optimised technique yielded a well-resolved dapagliflozin peak. The approach was validated by adhering to ICH criteria for specificity, linearity, accuracy, precision, and robustness. There was no influence from blank or placebo components, demonstrating excellent specificity. With a correlation coefficient (R2) of 0.9992, linearity was demonstrated across the concentration range of 25.614–102.457 μg/ ml. Precision experiments produced %RSD values less than 2.0%, and accuracy trials demonstrated a mean recovery of 99.5%. The method’s dependability under slight changes in chromatographic settings was validated by robustness tests. The test of commercial dapagliflozin tablets was successfully conducted utilising the validated Reverse Phase- High Performance Liquid Chromatography method, which was determined to be appropriate for routine quality control analysis.